Case of phaeohyphomycosis producing sporotrichoid lesions. Issue 8 (5th June 2013) - Hasei, Maki; Takeda, Kiminobu; Anzawa, Kazushi; Nishibu, Akiko; Tanabe, Hiroshi; Mochizuki, Takashi
Abstract: A 90‐year‐old Japanese woman, taking prednisolone (5–10 mg/day) for polyarthritis, presented to our hospital with multiple subcutaneous lesions on her left arm in 2009. Her history included excision of a phaeomycotic cyst on the left middle finger in 2007. There were three subcutaneous nodules approximately 15 mm in diameter around her left wrist and a large soft cystic lesion measuring 80 mm × 60 mm on her left elbow. A granuloma with neutrophilic infiltration was detected in the deep dermis of a biopsy specimen. Chains composed of round brown cells and short pseudomycelia were found in the granuloma. Fungal cultures from the samples confirmed Exophiala sp. to be the causative agent. Treatment with terbinafine and local hyperthermia seemed effective as all the lesions tended to subside. However, the patient died due to pneumonia approximately 1 month after commencement of therapy.